ACTUALIZATION OF THE FRAME IN LITERARY NARRATIVE (ON THE MATERIAL OF MODERN RUSSIAN PROSE) - Sergei Gusarenko; Marina Gusarenko (Гуманитарные и юридические исследования)
The relevance of the study lies in the fact that with all the diversity of studies on linguistic frames, the question of the pragmatics of language expressions representing a particular frame in the text (in our case, in the Russian narrative) is actual, in particular, what are those linguo-pragmatic means by which the frame is initiated in the narrative. The purpose of this article is to identify, describe and classify linguistic expressions, opening the actualization of the frame in the artistic narrative. The so-called ontological frames, representing stereotypical life situations and events in the text, were subjected to syntax structures corresponding to these frames. When analyzing the linguistic material, the following linguistic and pragmatic means initiating the actualization of the frame in the artistic narrative were identified: the name of the frame, the macroposition of the frame, the nuclear propositions of the frame, one of the slots of the updated frame, the interframe transition, the discursive presupposition. It is noted that frame initiation may be accompanied by textual implication operations, when the frame content is completed as a result of logical inference operations. Pragmatic presuppositions as front elements of actualized frames also act as means of their actualization, that is, in this case, pragmatic presuppositions can be considered as nuclear propositions of different frame levels. With rare exceptions, the frame in literary narrative is initiated by a set of linguistic and pragmatic means. At the same time, toponym-ic frames are actualized by means of the name of the frame and its nuclear propositions, but not by means of macropositions such as N is a city. The article notes that the set of means for initiating a frame is very diverse, while the analysis of the material showed that such means as the name of the frame or its slot, macropositions, nuclear propositions are more commonly used, and the most difficult question is whether the author chooses the text to initiate the frame.